Elevated 4-hydroxynonenal induces hyperglycaemia via Aldh3a1 loss in zebrafish and associates with diabetes progression in humans - Lou, Bowen; Boger, Mike; Bennewitz, Katrin; Sticht, Carsten; Kopf, Stefan; Morgenstern, Jakob; Fleming, Thomas; Hell, Rüdiger; Yuan, Zuyi; Nawroth, Peter Paul; Kroll, Jens (Redox Biology, 2020)
Increased methylglyoxal (MG) formation is associated with diabetes and its complications. In zebrafish, knockout of the main MG detoxifying system Glyoxalase 1, led to limited MG elevation but significantly elevated aldehyde dehydrogenases (ALDH) activity and aldh3a1 expression, suggesting the compensatory role of Aldh3a1 in diabetes. To evaluate the function of Aldh3a1 in glucose homeostasis and diabetes, aldh3a1−/− zebrafish mutants were generated using CRISPR-Cas9. Vasculature and pancreas morphology were analysed by zebrafish transgenic reporter lines. Corresponding reactive carbonyl species (RCS), glucose, transcriptome and metabolomics screenings were performed and ALDH activity was measured for further verification. Aldh3a1−/− zebrafish larvae displayed retinal vasodilatory alterations, impaired glucose homeostasis, which can be aggravated via pdx1 silencing induced hyperglycaemia. Unexpectedly, MG was not altered, but 4-hydroxynonenal (4-HNE), another prominent lipid peroxidation RCS exhibited high affinity with Aldh3a1, was increased in aldh3a1 mutants. 4-HNE was responsible for the retinal phenotype via pancreas disruption induced hyperglycaemia and can be rescued via l-Carnosine treatment. Furthermore, in type 2 diabetic patients, serum 4-HNE was increased and correlated with disease progression. Thus, our data suggest impaired 4-HNE detoxification and elevated 4-HNE concentration as biomarkers but also the possible inducers for diabetes, from genetic susceptibility to the pathological progression.
Gesehen am 08.02.2021